Increased baseline ECG R-R dispersion predicts improvement in systolic function after atrial fibrillation ablation. Issue 1 (25th June 2019) - Koene, Ryan J; Buch, Eric; Seo, Young-Ji; Li, Jian-Ming; Mbai, Mackenzi; Chandrashekhar, Y; Shivkumar, Kalyanam; Tholakanahalli, Venkatakrishna N
Abstract : Background: Atrial fibrillation (AF) is associated with left ventricular (LV) systolic dysfunction which may improve after AF ablation. We hypothesised that increased ventricular irregularity, as measured by R-R dispersion on the baseline ECG, would predict improvement in the left ventricular ejection fraction (LVEF) after AF ablation. Methods: Patients with LVEF <50% at two US centres (2007–2016), having both a preablation and postablation echocardiogram or cardiac MRI, were included. LVEF improvement was defined as absolute increase in LVEF by >7.5%. Multivariable logistic regression (restricted to echocardiographic/ECG variables) was performed to evaluate predictors of LVEF improvement. Results: Fifty-two patients were included in this study. LVEF improved in 30 patients (58%) and was unchanged/worsened in 22 patients (42%). Those with versus without LVEF improvement had an increased baseline R-R dispersion (645±155 ms vs 537±154 ms, p=0.02, respectively). The average baseline heart rate in all patients was 93 beats per minute. After multivariable logistic regression, increased R-R dispersion (OR 1.59, 95% CI 1.00 to 2.55, p=0.03) predicted LVEF improvement. Conclusions: Increased R-R dispersion on ECG was independently associated with improved systolic function after AF ablation. This broadens the existing knowledge of arrhythmia-induced cardiomyopathy, demonstrating that irregular electrical activation (as measured by increased R-R dispersion on ECG) is associated with a cardiomyopathy capable of improving after AF ablation.